Efeito do lodo de esgoto e do nitrogênio nos fatores produtivos do girassol - Lobo, Thomaz F. [UNESP]; Grassi Filho, Hélio [UNESP]; Büll, Leonardo Theodoro [UNESP]; Kummer, Ana C. B. [UNESP] (FapUNIFESP (SciELO), 2013)
In Brazil, among the various alternatives for final disposal of sewage sludge, agricultural use is notable for its economy and environmental compatibility. The objective of this study was to evaluate the effect of composted sewage sludge and N parameters on sunflower production after the sixth application of sewage sludge in different doses. The experiment was conducted at the Experimental Farm São Manuel-SP, belonging to the Faculty of Agronomic Sciences, UNESP, Botucatu-SP. The experimental design adopted was randomized blocks, consisting of six treatments and four replications defined as follows: T0 - without nitrogen fertilization; T1 - chemical nitrogen fertilizer in accordance with the recommendation for the crop; T2 - 50% nitrogen derived from sewage sludge and 50% in mineral form; T3 - 100% nitrogen from sewage sludge; T4 - 150% nitrogen from sewage sludge; T5 - 200% nitrogen from sewage sludge. Increasing the dose of sewage sludge and N provided an increase in grain yield, oil and dry matter. The N influenced the increase in the weight of thousand grans.
Effect of sewage sludge and nitrogen on production factors of sunflower
Keywords: Productivity and oil of yield; Sustainability